The economics of the enterprise for ASEAN initiative - Naya, Seiji; Plummer, Michael G. 1959- (Gale virtual reference library, 2005)
"This is a substantial exploration of many aspects of the Enterprise for ASEAN Initiatives (EAI) as envisaged in 2002 by the Bush administration in the United States. Included are discussions of the nature of US-ASEAN trade relations."--GVRL description.